Rehabilitation of human hearing with a totally implantable cochlear implant: a feasibility study - Philippe Pierre Lefebvre; Joachim Müller; Gerhard Mark; Florian Schwarze; Ingeborg Hochmair (Communications Medicine)
Abstract Background Cochlear implants (CIs) are neuroprosthetic devices which restore hearing in severe-to-profound hearing loss through electrical stimulation of the auditory nerve. Current CIs use an externally worn audio processor. A long-term goal in the field has been to develop a device in which all components are contained within a single implant. Here, we present initial clinical results with the totally implantable cochlear implant (TICI). The primary objective of this study was to assess the safety of the device in adults who suffer from bilateral severe-to-profound sensorineural hearing loss. Methods This study used a design with non-randomized single group assignment (trial registration: NCT04571333). Six implantations took place beginning in September 2020. Data collection took place at the two participating CI centers. Adverse events (the primary outcome), speech perception, patient reported outcomes, and device usage statistics were collected over the subsequent 52 weeks. A within-subjects comparison was used in which each participant was evaluated both with the TICI and with an external SONNET audio processor. Results One anticipated serious adverse device effect (ASADE) occurred. After treatment the event resolved without sequelae. No unanticipated serious adverse device effects (USADE) occurred. Speech perception in quiet and in noise scores were comparable between the TICI and the SONNET audio processor. Scores on the validated patient reported outcome instruments HUI3, SSQ-12, and HISQUI-19 all increased over the duration of the study. User satisfaction scores as reported in their daily diary also increased over the duration of the study. Based on device usage metrics, all but one user used the TICI without an external processor the majority of the time. Conclusions The primary outcome of assessing the safety of the device was achieved. The TICI provides high levels of hearing performance, comparable to those of a conventional CI. The development of the TICI expands the range of options for treatment of hearing loss.